Attitudes towards the Pasig River of residents in selected riverside barangays in Metro Manila and their implications to river rehabilitation - Deocariza, Mariño (2005)
The attitudes of Metro Manila residents towards the Pasig River have essentially declined by the turn of the 19th century. Pre-colonial settlers highly regarded the Pasig River because of its beneficial uses to the people. In the Spanish period the Pasig River was admired for its natural beauty and its invigorating breeze. Riverside properties were used as vacation houses of wealthy Spanish officials. The Spanish and American colonial governments considered the Pasig River to be politically and economically strategic, which explains why most of the key political and economic establishments during the colonial period were located along the banks of this river. Today, the river has extremely polluted and highly unattractive. The utilization of the river proceeded without care or concern amongst the people as indiscriminate dumping of wastes continues to aggravate its already sordid condition. Several efforts to rehabilitate the river briefly succeeded but fail in the long run as residential communities and business firms located as far as 20 kilometers away continue to pollute and defile the river. This research explores one aspect of river pollution that is often ignored yet is very essential in understanding and solving the problem- how people see, appreciate and value the Pasig River or the attitudes people hold towards the Pasig River. The research specifically aims to (1) describe the people's attitudes towards the Pasig River in the pre-colonial and colonial periods; (2) identify and assess the attitudes towards the Pasig River of present day residents in selected riverside communities in Metro Manila; and (3) determine the implications of the residents' prevailing attitudes towards the Pasig River to the ongoing efforts to rehabilitate the river..
"June 2005."
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Water -- Pollution -- Philippines -- Pasig River